Kontribusi Akuntansi Syariah terhadap Ekonomi Islam Terkait Pengembangan UMKM di Era Revolusi Teknologi: The Contribution of Sharia Accounting to Islamic Economics Regarding the Development of MSMEs in the Era of the Technological Revolution - Zahwa Praditha Eka Suci; Salsabila Nur Faizah; Bethany Enggar Sasetyaningjati; Nayla Nadhratunnaim (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This study aims to analyze the contribution of Islamic accounting to the strengthening of the Development of MSMEs in the era of technological revolution, as well as how Islamic accounting plays a role in the growth of Islamic finance in Indonesia in the modern era. This study was conducted using a literature study method by analyzing several journal sources relevant to the research topic. The results of this study show that the revolution will have a significant impact on the development of sharia-based accounting, especially in Indonesia. This is due to the fact that most workers in Indonesia are Muslim and are often associated with Islam. In addition to the impact of digitization on sharia accounting in Indonesia, digitization also brings challenges and opportunities for the accounting profession, especially sharia-based accountants, because they must readjust to Islamic teachings and existing technology. The number of accountants in the workforce will continue to decline as technology replaces accounting workers over time. Therefore, every accountant must have their own adaptation strategy to face the technological revolution.